Adsorption–desorption mechanism of a cationic polyelectrolyte based on dimethylaminoethyl polymethacrylates at the water/1,2-dichloroethane interface - Riva, Julieta Soledad (2013)
The electrochemical behaviour of the cationic polymer Eudragit® E100 at the polarized water/1,2-dichloroethane interface was studied. The voltammetric response was found to be dependent on the pH of the aqueous phase solution, on the nature of the organic electrolyte, and it was also time dependent during multi-cyclic voltammetry experiments. The results suggest that a diffusion process coupled to an adsorption or re-arrangement of E100 molecules at the interface is taking place. From the analysis of the desorption process, it was determined the presence of a strong attractive interaction between the adsorbed species at the interface and the lateral interaction parameter was calculated.